Characteristic x rays from multiple-electron capture by slow highly charged Taq+ ions from He and Xe atoms - Madzunkov, S.; Fry, D.; Lindroth, E.; Schuch, R. (My University, 2006)
Characteristic x rays, emitted by slow (velocity ν∼0.3a.u.) highly charged Taq+ (q=41–49) ions after multiple capture from He or Xe atoms, were investigated in coincidence with recoil ions. The x-ray spectra are distinctly different for single and double capture as well as for different target ionization potentials (He and Xe). For the open M-shell configurations of the projectile (q>45) the spectra are dominated by cascade transitions. There is no evidence for direct radiative transitions from Rydberg states into the M shell, indicating dominant capture into angular momentum states that forbids such transitions. From such features we get, by comparison with spectra obtained from the calculation of the radiative cascades, the angular momentum values of the captured electron. A simple model, including autoionization, is used to relate double- and single-capture x-ray spectra and to explain their differences. The x-ray spectra with projectiles having no initial M vacancies (q<45) can have an important contribution from the internal dielectronic excitation (IDE) process. It is found that this channel is drastically reduced for double capture from He and closed for projectiles with q=41, as expected from our calculations of the core-excited states in Ta(q−1)+. The x-ray spectra and photon yields in these heavy systems are thus determined by a competition between the relaxation channels: radiative relaxation, IDE, and, for multiple capture, autoionization.